Analysis of oral microbial community and Th17-associated cytokines in saliva of patients with oral lichen planus - Wang, Kun; Miao, Tianyu; Lu, Wenxin; He, Jinzhi; Cui, Bomiao; Li, Jiyao; Li, Yan; Xiao, Liying (Microbiology and immunology, 2015)
Oral lichen planus (OLP) is a chronic inflammatory disorder of oral mucosa of unknown cause. Microbial infection and dysimmunity appear to play important roles in its pathogenesis. In this study, differences in genetic profiling of salivary microbial communities in two subtypes of OLP and healthy controls were evaluated by means of PCR-denaturing gradient gel electrophoresis (DGGE). Additionally, ELISA was used to investigate the possible role of Th17 in lesion formation by detecting two related cytokines IL-17 and IL-23 in the saliva of OLP patients. When the DGGE profiles were analyzed, the bacterial populations were found to be significantly less rich in subjects with reticular and erosive OLP than in healthy controls. There was significantly less microbial diversity, as denoted by the Shannon index, in saliva samples from subjects with erosive OLP than in those from healthy controls. Cluster analysis and principal component analysis showed that the DGGE profiles formed distinctly group-specific clusters. Salivary concentrations of IL-17 in subjects with erosive OLP group were significantly higher than in those with reticular OLP and healthy controls. What's more, significantly positive correlations were observed between salivary IL-17 concentrations and disease clinical scores. Microbial richness and diversity was negatively correlated with salivary IL-17 concentrations. These results suggest there is significantly less salivary bacterial diversity and complexity in subjects with OLP han in healthy controls and that the shifted community composition is closely related to an immune cytokine, IL-17.